A qualitative study on active ageing and development of active ageing questionnaire among the elderly in Malaysia - Esa, Wafaak (2018)
Background: Active ageing is a conceptual understanding of ageing well and may affect on the quality of life. Therefore accurate measurement of active ageing is important in health of the elderly. Objective: To explore the perception, determinants, and to develop and validate an instrument measuring level of active ageing among the elderly in Malaysia. Method: Phase 1: A qualitative study using phenomenology tradition was carried out in all five regions of Malaysia. A purposive sampling was applied among the members of Persatuan Pesara Kerajaan and Kelab Warga Emas. Data was collected through nine focus group discussions and 19 in-depth interviews. Thematic analysis was carried out. Phase 2: Result from phase 1 informed development of the scale, Active Ageing Questionnaire. Three domains with 82 items were developed and went through content and face validation. Construct, criterion validation and reliability test were carried out on 302 elderly. Convenient sampling was applied among members of same organisations. World Health Organization Quality of Life Assessment Brief Version in Malay language was also used for criterion validation. Content validation index, face validation index, exploratory factor analysis, Pearson Correlation and Cronbach’s Alpha analysis were carried out. Results: The participants were mixture of multiracial, gender and between 60 to 80 years old. Three emergent themes of active ageing were independence, participation and positive emotion effect. In Malaysia, active ageing is a process of doing activity independently, as a continuity and optimisation of life through participation which bring benefit to the self, family and community, and resulting in a positive emotional effect to life. These informed the Active Ageing Questionnaire development which showed an excellent content and face validation index. Three factors, independent, participation and satisfaction, were extracted with 20 items each. There were significant positive strong correlations between Active Ageing Questionnaire score and World Health Organization Quality of Life Assessment Brief Version score. The Cronbach’s Alpha value was 0.96 for overall value; for independence, participation and satisfaction domain these were 0.95, 0.93 and 0.92 respectively. Conclusion: The conceptual active ageing understanding among Malaysia’s elderly is multidimensional and has similarities to the model by World Health Organization. There is a complex interaction between body and environment. The Active Ageing Questionnaire showed a good validity and reliability for measuring active ageing level among elderly in Malaysia. This will allow measurement of active ageing to inform policy development